2022
DOI: 10.1126/sciadv.abq8109
|View full text |Cite
|
Sign up to set email alerts
|

Functional specialization of different PI3K isoforms for the control of neuronal architecture, synaptic plasticity, and cognition

Abstract: Neuronal connectivity and activity-dependent synaptic plasticity are fundamental properties that support brain function and cognitive performance. Phosphatidylinositol 3-kinase (PI3K) intracellular signaling controls multiple mechanisms mediating neuronal growth, synaptic structure, and plasticity. However, it is still unclear how these pleiotropic functions are integrated at molecular and cellular levels. To address this issue, we used neuron-specific virally delivered Cre expression to delete either p110α or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Some research suggested that CCI may lead to neurological damage and consequently cognitive impairment through a variety of mechanisms, including synaptic damage, neurotransmitter disruption, oxidative stress, and neuroinflammatory responses (Daulatzai, 2017; Feng et al., 2012; Xi et al., 2014; Zhao et al., 2014). In our study, it was revealed that CCI increased apoptosis of neurons, inhibited pro‐survival PI3K/Akt signaling, which plays an essential role in the growth, survival, and differentiation of neuronal cells and the maintenance of synaptic plasticity (Razani et al., 2021; Sánchez‐Castillo et al., 2022; Shu et al., 2013). Accordingly, the PI3K/Akt pathway may contribute to the neuroprotective effects of the interventions in our study on cognitive impairment after CCI.…”
Section: Discussionmentioning
confidence: 85%
“…Some research suggested that CCI may lead to neurological damage and consequently cognitive impairment through a variety of mechanisms, including synaptic damage, neurotransmitter disruption, oxidative stress, and neuroinflammatory responses (Daulatzai, 2017; Feng et al., 2012; Xi et al., 2014; Zhao et al., 2014). In our study, it was revealed that CCI increased apoptosis of neurons, inhibited pro‐survival PI3K/Akt signaling, which plays an essential role in the growth, survival, and differentiation of neuronal cells and the maintenance of synaptic plasticity (Razani et al., 2021; Sánchez‐Castillo et al., 2022; Shu et al., 2013). Accordingly, the PI3K/Akt pathway may contribute to the neuroprotective effects of the interventions in our study on cognitive impairment after CCI.…”
Section: Discussionmentioning
confidence: 85%
“…It is involved in synaptic plasticity and memory formation in various brain areas, including hippocampal Schaffer-CA1 synapses, dentate gyrus, and amygdala (Chen et al 2005 ). PI3K is responsible for important events in memory formation, such as the insertion of AMPA receptors into the postsynaptic membrane and the initiation of protein synthesis (Chen et al 2005 ; Sánchez-Castillo et al 2022 ). Activation of the PI3K pathway promotes cell survival, acts on downstream mTOR to facilitate protein synthesis, and may be implicated in synaptic plasticity and memory consolidation (Horwood et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Field recordings were performed on coronal slices containing the hippocampus as previously described ( 80 , 81 ). Briefly, animals were anesthetized by isoflurane inhalation (Esteve) and decapitated.…”
Section: Methodsmentioning
confidence: 99%